Adoption of Improved Practices and Annual Fish Catches among Mechanised Boat Owners - S., Balasubramaniam; P., Pravin; J.M., Sreevalsan; Mohan, Braj (Fishery Technology, 2025)
This paper deals with the adoption of improved practices and annual fish catches among mechanized fishing boat owners in six fishing centers. The results revealed that in Gujarat, Veraval center had higher adoption of improved technologies (61.16%), followed by Mangrol (56.64%) and Porbundar (49.92%). The adoption scores in the Kerala fishing centers were in the high category (>85%). The annual average fish catches in the fishing centers of Gujarat were found to be above 78 t and in Kerala, it was higher in Cochin (95.29 t) followed by Kozhikode (39.47 t) and Quilon (28.90 t). Regression analyses on the adoption scores among Gujarat respondents revealed that three variables viz., investment on boat, number of trawl nets operated and awareness about improved practices would have to be strengthened to increase the extent of adoption of improved practices. Further, sixteen socio-personal and technological variables were found to have significant joint influence (>81%) on the annual fish catches in the three fishing centers